A systematic analysis of circRNAs in subnuclear compartments - Andre Brezski; Justin Murtagh; Marcel H. Schulz; Kathi Zarnack (RNA Biology)
CircRNAs are an important class of RNAs with diverse cellular functions in human physiology and disease. A thorough knowledge of circRNAs including their biogenesis and subcellular distribution is important to understand their roles in a wide variety of processes. However, the analysis of circRNAs from total RNA sequencing data remains challenging. Therefore, we developed Calcifer, a versatile workflow for circRNA annotation. Using Calcifer, we analysed APEX-Seq data to compare circRNA occurrence between whole cells, nucleus and subnuclear compartments. We generally find that circRNAs show higher abundance in whole cells compared to nuclear samples, consistent with their accumulation in the cytoplasm. The notable exception is the single-exon circRNA circCANX(9), which is unexpectedly enriched in the nucleus. In addition, we observe that circFIRRE prevails over the linear lncRNA FIRRE in both the cytoplasm and the nucleus. Zooming in on the subnuclear compartments, we show that circRNAs are strongly depleted from nuclear speckles, indicating that excess splicing factors in this compartment counteract back-splicing. Our results thereby provide valuable insights into the subnuclear distribution of circRNAs. Regarding circRNA function, we surprisingly find that the majority of all detected circRNAs possess complete open reading frames with potential for cap-independent translation. Overall, we show that Calcifer is an easy-to-use, versatile and sustainable workflow for the annotation of circRNAs which expands the repertoire of circRNA tools and allows to gain new insights into circRNA distribution and function.